2020
DOI: 10.1177/0145561320942368
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Nasal Pyriform Aperture Stenosis: Successful Management of Restenosis After Primary Surgery by Stent Placement

Abstract: Congenital nasal pyriform aperture stenosis (CNPAS) is a rare anomaly causing respiratory distress in newborns. While the primary surgical technique is well established, the timing of the removal of the stents and the management of restenosis remain a matter of debate. We report a case of a female newborn affected by CNPAS with the recurrence of respiratory distress after primary surgery due to the early removal of nasal stents, causing an overgrowth of granulation tissue. This report notes that restenosis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Botti et al reported that stent removal at four days after the first surgery caused restenosis in the nasal cavities and relapse of respiratory distress and the patient eventually required a second surgery [18]. Although the duration of stenting is variable [17], it is recommended that stents be left in place for approximately one to two weeks [16,18,19]. In the current case, the stent was placed for two weeks, and no restenosis was observed four months postoperatively.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Botti et al reported that stent removal at four days after the first surgery caused restenosis in the nasal cavities and relapse of respiratory distress and the patient eventually required a second surgery [18]. Although the duration of stenting is variable [17], it is recommended that stents be left in place for approximately one to two weeks [16,18,19]. In the current case, the stent was placed for two weeks, and no restenosis was observed four months postoperatively.…”
Section: Discussionmentioning
confidence: 78%
“…After surgery, stent placement is recommended to prevent restenosis and granulation. In addition to endotracheal tubes, soft silastic nasal stents and standard nasal conformers, usually employed in cleft surgery, are used for stents [3,18]. Botti et al reported that stent removal at four days after the first surgery caused restenosis in the nasal cavities and relapse of respiratory distress and the patient eventually required a second surgery [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sublabial surgical approach has historically been shown to be safe and associated with good surgical outcomes. 24,25 The exposure achievable with this technique prevents damage to soft tissues and avoids visible external scarring. The results are apparent immediately after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…These include injury to the nasal mucosa, nasolacrimal duct, tooth buds, and nasal ala, as well as septal ulceration and postoperative granulation tissue formation causing re-stenosis. 17,25,26…”
Section: Discussionmentioning
confidence: 99%